UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA TENTANG MENGGOLONGKAN HEWAN BERDASARKAN JENIS MAKANAN DENGAN METODE PEMECAHAN MASALAH (PROBLEM SOLVING) PADA SISWA KELAS IV DI SDN SUKAONENG KECAMATAN TAMBAK KABUPATEN GRESIK - Kamilah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
: The purpose of this action research is: (a) want to know the improvement of student's learning achievement after the application of learning problem solving method, (b) to know the influence of student's learning motivation after applying the learning problem solving method. This research uses action research for three rounds. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is the fourth grade students of SDN Sukaoneng Kecamatan Tambak of Gresik Regency in the academic year 2015/2016. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analyst's result, it is found that students' learning achievement has increased from cycle I and cycle II that is, cycle I (46,15%), cycle II (84,62%), From the results of cycles I and II proved to have increased learning mastery of 38.47% so it can be said the method of problem solving (problem solving) can improve student achievement in grade IV SDN Sukaoneng. The conclusion of this research is problem solving method can improve student's learning achievement and can have a positive effect on learning motivation of fourth grade students of SDN Sukaoneng Tambak Sub-district of Gresik Regency in the lesson year 2015/2016, and this learning model can be used as one of alternative learning IPA